An AN ANALYSIS OF ONE HAPPY DAY BY SHRILAL SHUKLA THROUGH THE LENS OF LAUGHTER BY HENRI BERGSON - Bragantin, Thiago Gomes da Gama (ShodhGyan-NU: Journal of Literature and Culture Studies, 2026)
This article proposes a literary and philosophical analysis of the short story One Happy Day from the book Selected Satire by Indian author Shrilal Shukla, using Henri Bergson's work Laughter (1900) as a theoretical framework. The short story narrates an atypical day in the life of a protagonist who finds himself surrounded by unusual order and tranquility, where the small mechanical obstacles of daily life disappear. Through the application of Bergsonian concepts of “the mechanical embedded in the living”, “rigidity” and “automatism” we explore how Shukla 's humor emerges not from the presence of explicit comedy, but from the absence of the social and physical rigidities that normally make life absurd. The analysis demonstrates that the narrator's “happiness” is, in fact, a satire on the mechanical nature of society and human interactions, revealing that normality, in Bergson's view, is a set of automatisms that laughter seeks to correct.